Analysis of codon usage bias of classical swine fever virus - Patil, Sharanagouda S. (Vet World, 2021)
BACKGROUND AND AIM: Classical swine fever (CSF), caused by CSF virus (CSFV), is a highly contagious disease in pigs causing 100% mortality in susceptible adult pigs and piglets. High mortality rate in pigs causes huge economic loss to pig farmers. CSFV has a positive-sense RNA genome of 12.3 kb in length flanked by untranslated regions at 5’ and 3’ end. The genome codes for a large polyprotein of 3900 amino acids coding for 11 viral proteins. The 1300 codons in the polyprotein are coded by different combinations of three nucleotides which help the infectious agent to evolve itself and adapt to the host environment. This study performed and employed various methods/techniques to estimate the changes occurring in the process of CSFV evolution by analyzing the codon usage pattern. MATERIALS AND METHODS: The evolution of viruses is widely studied by analyzing their nucleotides and coding regions/codons using various methods. A total of 115 complete coding regions of CSFVs including one complete genome from our laboratory (MH734359) were included in this study and analysis was carried out using various methods in estimating codon usage bias and evolution. This study elaborates on the factors that influence the codon usage pattern. RESULTS: The effective number of codons (ENC) and relative synonymous codon usage showed the presence of codon usage bias. The mononucleotide (A) has a higher frequency compared to the other mononucleotides (G, C, and T). The dinucleotides CG and CC are underrepresented and overrepresented. The codons CGT was underrepresented and AGG was overrepresented. The codon adaptation index value of 0.71 was obtained indicating that there is a similarity in the codon usage bias. The principal component analysis, ENC-plot, Neutrality plot, and Parity Rule 2 plot produced in this article indicate that the CSFV is influenced by the codon usage bias. The mutational pressure and natural selection are the important factors that influence the codon usage bias. CONCLUSION: The study provides useful information on the codon usage analysis of CSFV and may be utilized to understand the host adaptation to virus environment and its evolution. Further, such findings help in new gene discovery, design of primers/probes, design of transgenes, determination of the origin of species, prediction of gene expression level, and gene function of CSFV. To the best of our knowledge, this is the first study on codon usage bias involving such a large number of complete CSFVs including one sequence of CSFV from India.